The Effectiveness of Local Taxes on Local Revenue of Bojonegoro Regency - Putra, Ringga Ananta; Iswanto, Denny (Polytechnic of State Finance STAN, 2024)
This study aims to examine the effectiveness of local taxes in Bojonegoro Regency in increasing local revenue. The data shows that the effectiveness of local taxes consistently exceeds 100%, indicating a very high level of effectiveness. The growth of local tax realization in real terms also shows a positive trend. Results and discussion include analysis of local tax effectiveness based on actual local tax data, comparison with previous research, research limitations, and deductive arguments. The conclusion contains a summary of the results and discussions that refers to the research objectives and suggestions for further research. In addition, this study presents a collection of academic journal articles focusing on consumer satisfaction, purchase decisions, and the impact of corporate brand symbolism on consumer satisfaction and loyalty. The article also includes tables with factor loadings for various measurement items relating to empathy, delivery service, reliability, brand image, product quality, price satisfaction, food quality, promotion satisfaction, and consumer hospitality. The research methodology uses quantitative methods with a descriptive approach, analyzing data from 2015 to 2019. Local tax effectiveness is calculated using a specific formula. This article aims to provide a deeper understanding of the impact of local taxes on local revenue and contribute to the literature on local tax effectiveness, particularly in the context of Bojonegoro Regency. Overall, this research offers insights into local tax effectiveness, its implications for local revenue, and broader implications for consumer satisfaction and loyalty in the context of corporate branding.